The diagnostic value of cytology in parotid Warthin's tumors: international multicenter series. Issue 3 (24th November 2019) - Borsetto, Daniele; Fussey, Jonathan M.; Cazzador, Diego; Smith, Joel; Ciorba, Andrea; Pelucchi, Stefano; Donà, Sara; Boscolo‐Rizzo, Paolo; Tomasoni, Michele; Lombardi, Davide; Nicolai, Piero; Zanoletti, Elisabetta; et al.
Abstract: Introduction: Warthin's tumor (WT) is a common benign salivary gland neoplasm with a negligible risk of malignant transformation. However, there is a risk of malignant tumors being misdiagnosed as WT on cytology and inappropriately managed conservatively. Methods: Patients from nine centers in Italy and the United Kingdom undergoing parotid surgery for cytologically diagnosed WT were included in this multicenter retrospective series. Definitive histology was compared with preoperative cytological diagnoses. Surgical complications were recorded. Results: A total of 496 tumors were identified. In 88.9%, the final histological diagnosis was WT. In 21 cases (4.2%) a malignant neoplasm was diagnosed, which had been incorrectly labeled as WT on cytology. Conclusions: The risk of undiagnosed malignancy should be balanced against surgical risks when considering the management of WT. Although nonsurgical management remains an appropriate option, there may be a rationale for serial clinical or radiological evaluation if surgical excision is not performed.